Taşrada Kent ve Aydın: Bursa Örneği (1930-1950) - Ulusoy, Can (Politics, 2021)
This work, discussing the relationship between the city and the intellectual in the countryside through the example of Bursa, from a time section, is a source that can be considered as a reference book for researchers who are engaged in social sciences such as elite circulation theories, elite and intellectual concepts, political-cultural debates over space, social memory construction processes shaped by political imaginations, and historiography and readers who are interested in such fields. The author aimed to embody such concepts and theories by questioning the relationships between structures and actors in the aura of historical ground and time. Therefore, it is essential to emphasize that the title of the study submitted to the attention of the reader should not be considered as a reflection of time and space boundaries, of the minimalist and micro-historical view of the post-modern understanding, and that it is acted on a concrete plane with a structural-historical method. When considered from this point of view, the work at hand is brought to the attention of all social scientists, especially those who are involved in political culture, Turkish political life, political science, urbanization and architectural history.